An uncommon chronic osteochondral defect in the lateral tibial plateau detected after a separate injury. (7th March 2018) - Leung, Raymond; Thomas, Panos
Abstract : Osteochondral defects (OCD) are rare conditions that usually present in young adolescents. The causes include trauma, inflammation, ischaemia, genetics and changes at secondary ossification centres. The case report presents a 27-year-old man with chronic intermittent left knee pain for about 3 years. He typically develops the symptom after prolonged standing or when rising from a prolonged seated position. An initial MRI scan in 2014 did not identify and report an OCD that was present in his left lateral tibial plateau. It was only after an accidental tibial fracture injury this year that the defect was incidentally detected on a scan. OCD can be staged based on MRI and/or arthroscopic findings. The treatment can be either non-operative or operative, but this largely depends on the age of the patient, the severity of symptoms and the staging of the defect.